The Operational Practices of Selected Private Higher Education Institutions in Agusan Del Norte - Coraza, Russellene B.; Matheu Jr., Emilio D. (Randwick International of Education and Linguistics Science Journal, 2025)
This research intended to study the operational practices of selected private higher education institutions in Agusan del Norte. Specifically, it sought to determine the extent to which operational practices are observed by the HEIs in the areas of: forecasting, enrolment promotional activities, capacity planning and expansion, and facilities and equipment upgrading. Using the descriptive survey method and with the aid of a researcher-made questionnaire, the following findings were established: 1) the practices of HEIs in the areas of forecasting, enrolment and promotional activities, and capacity planning and expansion were rated to a great extent, while the facilities and equipment upgrading was rated to a very great extent; 2) there is no significant difference in responses among schools using Friedman’s test; and 3) there is a significant difference in certain areas between positions of respondents using ANOVA test.